Auditory Cortical Maturation in a Child with Cochlear Implant: Analysis of Electrophysiological and Behavioral Measures - Liliane Aparecida Fagundes Silva; Maria Inês Vieira Couto; Robinson Koji Tsuji; Ricardo Ferreira Bento; Ana Claudia Martinho de Carvalho; Carla Gentile Matas (Case Reports in Otolaryngology)
The purpose of this study was to longitudinally assess the behavioral and electrophysiological hearing changes of a girl inserted in a CI program, who had bilateral profound sensorineural hearing loss and underwent surgery of cochlear implantation with electrode activation at 21 months of age. She was evaluated using the P1 component of Long Latency Auditory Evoked Potential (LLAEP); speech perception tests of the Glendonald Auditory Screening Procedure (GASP); Infant Toddler Meaningful Auditory Integration Scale (IT-MAIS); and Meaningful Use of Speech Scales (MUSS). The study was conducted prior to activation and after three, nine, and 18 months of cochlear implant activation. The results of the LLAEP were compared with data from a hearing child matched by gender and chronological age. The results of the LLAEP of the child with cochlear implant showed gradual decrease in latency of the P1 component after auditory stimulation (172 ms–134 ms). In the GASP, IT-MAIS, and MUSS, gradual development of listening skills and oral language was observed. The values of the LLAEP of the hearing child were expected for chronological age (132 ms–128 ms). The use of different clinical instruments allow a better understanding of the auditory habilitation and rehabilitation process via CI.